US Older Adults That Consume Avocado or Guacamole Have Better Cognition Than Non-consumers: National Health and Nutrition Examination Survey 2011–2014 - Cheng, Feon W.; Ford, Nikki A.; Taylor, Matthew K. (Frontiers in Nutrition, 2021)
Purpose: The goal of this study is to examine how avocado relates to cognitive function among older adults. Methods: A total of 2,886 National Health and Nutrition Examination Survey 2011-2014 participants aged 60 or older met the eligibility criteria and were included of our cross-sectional study. Participants were binarily classified as avocado consumers (i.e., reported consuming any avocado/guacamole in either 24-hour dietary recalls) or non-consumers. Cognitive performance was evaluated with: Consortium to Establish a Registry for Alzheimer’s disease (CERAD) – immediate and delayed recall (IWR/DWR), the Animal Fluency test, and the Digit Symbol Substitution Test. We calculated the education-dependent z-scores for each subject because education level can impact cognitive function. Global cognitive score, an average of the z-scores for each cognitive test, was calculated in participants who had completed all four tests. To account for relevant covariates, we tested for mean differences in cognition between consumers and non-consumers using independent sample t-tests and ANCOVA, special cases of ordinary least squares regression. Results: Avocado consumers had significantly better cognitive scores across all cognitive tests and the global cognition score (p<0.05) in the unadjusted model. Some mean differences attenuated after adjusting for potential confounders, but others remained significant. Compared to non-consumers, avocado consumers had significantly higher z-scores of 0.15, 0.15, and 0.11 for CERAD IWR and DWR, and global cognition score, respectively (all p<0.05 in adjusted models). Conclusion: Avocado consumption was associated with significantly better IWR, DWR, and the overall global cognition score, which remained significant when controlling for all relevant confounders.